Repetitive TMS Suggests a Role of the Human Dorsal Premotor Cortex in Action Prediction - Stadler, Waltraud; Ott, Derek V.; Springer, Anne; Schubotz, Ricarda I.; Schütz-Bosbach, Simone; Prinz, Wolfgang (Frontiers in Human Neuroscience, 2012)
Predicting the actions of other individuals is crucial for our daily interactions. Recent evidence suggests that the prediction of object-directed arm and full-body actions employs the PMd. Thus, the neural substrate involved in action control may also be essential for action prediction. Here, we aimed to address this issue and hypothesised that disrupting the PMd impairs action prediction. Using fMRI-guided coil navigation, rTMS (5 pulses, 10 Hz) was applied over the left PMd and over the vertex (control region) while participants observed everyday actions in video clips that were transiently occluded for one second. The participants detected manipulations in the time course of occluded actions, which required them to internally predict the actions during occlusion. To differentiate between functional roles that the PMd could play in prediction, rTMS was either delivered at occluder onset (TMS-early), affecting the initiation of action prediction, or 300 ms later during occlusion (TMS-late), affecting the maintenance of an ongoing prediction. TMS-early over the left PMd produced more prediction errors than TMS-early over the vertex. TMS-late had no effect on prediction performance, suggesting that the left PMd might be involved particularly during the initiation of internally guided action prediction but may play a subordinate role in maintaining ongoing prediction. These findings open a new perspective on the role of the left PMd in action prediction which is in line with its functions in action control and in cognitive tasks. In the discussion, the relevance of the left PMd for integrating external action parameters with the observer’s motor repertoire is emphasised. Overall, the results are in line with the notion that premotor functions are employed in both action control and action observation.